Why do we love pandas and hate cockroaches? - Albuquerque, Ulysses Paulino; Silva, João Victor Mendes (Ethnobiology and Conservation, 2024)
This review explores the intricate interplay of human emotions towards different animal species. It delves into the contrasting feelings we harbor towards appealing animals like pandas and our aversion towards others like cockroaches. Drawing from the evolutionary ethnobiology perspective, it uncovers how biophilia and biophobia, deeply rooted in our evolutionary past, shape our reactions to various species. We also examine the role of the Behavioral Immune System (BIS) in our aversion to pathogen-carrying arthropods, the impact of educational interventions on changing attitudes toward wildlife, and the influence of animation on human memory and attention. We underscore the significance of understanding these psychological mechanisms in conservation strategies. We highlight how the evolutionary naturalist mind, influenced by ancestral threats and contemporary challenges, is pivotal in fostering a more harmonious coexistence with nature.